(untitled) (Indian Journal of Child Health, 2015)
Patients with disseminated tuberculosis (TB) have varied presentations like pyrexia of unknown origin, hepatosplenomegaly, lymphadenopathy and meningitis, but pancytopenia is rare. Sometimes the cause of pancytopenia is not discernible after initial investigations. Such cases need further evaluation to know the etiology of pancytopenia for appropriate management of the patient. The present case was misdiagnosed as nutritional anaemia, which after thorough workup was diagnosed as disseminated TB. We are reporting this case in view of extreme rarity of TB presenting with pancytopenia.